Observation of pressure induced charge density wave order and eightfold structure in bulk VSe2 - Zhiying Guo (Nature Portfolio, 2021)
Abstract Pressure-induced charge density wave (CDW) state can overcome the low-temperature limitation for practical application, thus seeking its traces in experiments is of great importance. Herein, we provide spectroscopic evidence for the emergence of room temperature CDW order in the narrow pressure range of 10–15 GPa in bulk VSe2. Moreover, we discovered an 8-coordination structure of VSe2 with C2/m symmetry in the pressure range of 35–65 GPa by combining the X-ray absorption spectroscopy, X-ray diffraction experiments, and the first-principles calculations. These findings are beneficial for furthering our understanding of the charge modulated structure and its behavior under high pressure.